Fire-derived organic carbon in soil turns over on a centennial scale - N. Singh; S. Abiven; M. S. Torn; M. W. I. Schmidt (Biogeosciences, 2012)
Pyrogenic carbon (PyC), the residue of an incomplete combustion of biomass, is considered as a carbon (C) sink due to its assumed stability in soil. PyC turnover time estimated using two modelling approaches, based on data from 16 published studies (n = 54) on PyC degradation, ranged from a decadal to centennial time scale, varying with initial biomass type, pyrolysis temperature, and incubation or field study. The average turnover time using a one-pool approach was 88 y, and the best estimate using a two-pool approach was 3 y for a fast-cycling pool and 870 y for a slow-cycling pool. Based on this meta-analysis, PyC cannot be assumed to persist in soils for thousands of years, and its use as a strategy for offsetting carbon emissions requires prudence and further research.